Constraint-induced or multi-modal personalized aphasia rehabilitation (COMPARE): A randomized controlled trial for stroke-related chronic aphasia. Issue 9 (December 2019) - Rose, Miranda L; Copland, David; Nickels, Lyndsey; Togher, Leanne; Meinzer, Marcus; Rai, Tapan; Cadilhac, Dominique A; Kim, Joosup; Foster, Abby; Carragher, Marcella; Hurley, Melanie; Godecke, Erin
Rationale: The comparative efficacy and cost-effectiveness of constraint-induced and multi-modality aphasia therapy in chronic stroke are unknown. Aims and hypotheses: In the COMPARE trial, we aim to determine whether Multi-Modal Aphasia Treatment (M-MAT) and Constraint-Induced Aphasia Therapy Plus (CIAT-Plus) are superior to usual care (UC) for chronic post-stroke aphasia. Primary hypothesis: CIAT-Plus and M-MAT will reduce aphasia severity (Western Aphasia Battery-Revised Aphasia Quotient (WAB-R-AQ)) compared with UC: CIAT-Plus superior for moderate aphasia; M-MAT superior for mild and severe aphasia. Sample size estimates: A total of 216 participants (72 per arm) will provide 90% power to detect a 5-point difference on the WAB-R-AQ between CIAT-Plus or M-MAT and UC at α = 0.05. Methods and design: Prospective, randomized, parallel group, open-label, assessor blinded trial. Participants: Stroke >6 months; aphasia severity categorized using WAB-R-AQ. Computer-generated blocked and stratified randomization by aphasia severity (mild, moderate, and severe), to 3 arms: CIAT-Plus, M-MAT (both 30 h therapy over two weeks); UC (self-reported usual community care). Study outcomes: WAB-R-AQ immediately post-intervention. Secondary outcomes: WAB-R-AQ at 12-week follow-up; naming scores, discourse measures, Communicative Effectiveness Index, Scenario Test, and Stroke and Aphasia Quality of Life Scale-39 g immediately and at 12 weeks post-intervention; incremental cost-effectiveness ratios compared with UC at 12 weeks. Discussion: This trial will determine whether CIAT-Plus and M-MAT are superior and more cost-effective than UC in chronic aphasia. Participant subgroups with the greatest response to CIAT-Plus and M-MAT will be described.